Accelerated SQL Server 2008 - Coles, Michael; Ferracchiati, Fabio Claudio; Walters, Robert; Farmer, Chris; Rae, Jonathan (Apress : Imprint: Apress, 2008)
The expert tuition and approach to rapid learning in Accelerated SQL Server 2008, one of the first SQL Server 2008 books available, will enable SQL Server and other database professionals to make the leap to the 2008 release of Microsoft's flagship database management system quickly. Take full advantage of the features of SQL Server 2008, know what tools are available, and quickly realize the power and ease of use that SQL Server 2008 has to offer. Lightning-fast introduction to SQL Server 2008 Written by top experts in the field Provides a solid grounding in key features and technologies.